Mesencephalic basolateral domain specification is dependent on Sonic Hedgehog - Jesus E. Martinez-Lopez; Juan A Moreno-Bravo; M. Pilar eMadrigal; Salvador eMartinez; Salvador eMartinez; Eduardo ePuelles (Frontiers Media S.A., 2015)
In the study of central nervous system morphogenesis, the identification of new molecular markers allows us to identify domains along the antero-posterior and dorso-ventral axes. In the past years, the alar and basal plates of the midbrain have been divided into different domains. The precise location of the alar-basal boundary is still under discussion. We have identified Barhl1, Nhlh1 and Six3 as appropriate molecular markers to the adjacent domains of this transition. The description of their expression patterns and the contribution to the different mesencephalic populations corroborated their role in the specification of these domains. We studied the influence of Sonic Hedgehog on these markers and therefore on the specification of these territories. The lack of this morphogen produced severe alterations in the expression pattern of Barhl1 and Nhlh1 with consequent misspecification of the basolateral domain. Six3 expression was apparently unaffected, however its distribution changed leading to altered basal domains. In this study we confirmed the localization of the alar-basal boundary dorsal to the basolateral domain and demonstrated that the development of the basolateral domain highly depends on Shh.